The Intravenous Laser Blood Irradiation in Chronic Pain and Fibromyalgia - Momenzadeh, Sirous; Abbasi, Mohammadzaki; Ebadifar, Asghar; Aryani, Mohammadreza; Bayrami, Jafar; Nematollahi, Fatemeh (Journal of Lasers in Medical Sciences, 2014)
Intravenous laser blood irradiation was first introduced into therapy by the Soviet scientists EN.Meschalkin and VS.Sergiewski in 1981. Originally this method was developed for the treatment of cardiovascular diseases. Improvement of rheologic properties of the blood as well as improvement of microcirculation and reduction of the area of infarction has been proved. Further, reduction of dysrhythmia and sudden cardiac death was achieved. At first, only the Helium-Neon laser (632.8 nm) was used in this therapy. For that, a power of 1-3mW and a period of exposure of 20-60 minutes were applied. The treatments were carried out once or twice a day up to ten appointments in all1. In the years after, many, and for the most part Russian studies showed that helium-neon laser had various effects on many organs and on the hematologic and immunologic system. The studies were published mainly in Russian which were little known in the West because of decades of political separation, and were regarded with disapproval. Besides clinical research and application for patients, the cell biological basis was developed by the Estonian cell biologist Tiina Karuat the same time. An abstract is to be found in her work “The Science of Low-Power Laser-Therapy”